TRADISI MANDI SAFAR SEBAGAI WISATA BUDAYA DI KECAMATAN RUPAT UTARA KABUPATEN BENGKALIS TAHUN 1989-2018 - Kalvin, Kalvin; Isjoni, Isjoni; Ibrahim, Bedriati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: One of the traditions that developed in Bengkalis Regency is the activity in the month of Safar. The safari bathing tradition is a spiritual attempt at self-approach to God, performed by some Muslim communities in different areas in Bengkalis Regency, right in Tanjung Punak Village Rupat Island, Bengkalis Regency, Riau Province. The safari bathing tradition that was held last Wednesday in the month of Safar with the aim of rejecting reinforcements. The local government has determined that the Safar swimming ritual is an asset of local wisdom and an annual tourist attraction expected to attract domestic and foreign tourists. The aim of this study is 1) To find out the origin of the tradition of safari bathing in the month of Safar in the Rupat Utara District, Tanjung Punak Village. 2) To find out the process of implementation of the Safar bath tradition, 3) To find out the values of the Safar bath tradition. 4) To know the development of the Safar Mandi tradition as cultural tourism, 5) To discover the role of the local government in preserving the Safar Mandi tradition as cultural tourism. Data analysis using qualitative methods and then using the comparative method. The results of this study are the Mandi Safar tradition, which is one of the ancestral legacies believed to be able to reject setbacks (accidents, disasters and epidemics), from the procedures and values in the Mandi Safar tradition that may benefit for those who carry it out and watched the Mandi Safar program. Apart from that, the role of the local government in developing and maintaining the Mandi Safar tradition is also very important in promoting the village and economy of the people of Tanjung Punak Village, Rupat Utara District, Bengkalis Regency.Key Words: Safar Mandi Tradition, Cultural Tourism, District of North Rupat,Bengkalis Regency.